2006
DOI: 10.1073/pnas.0600345103
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Cell–cell signaling in Xanthomonas campestris involves an HD-GYP domain protein that functions in cyclic di-GMP turnover

Abstract: HD-GYP is a protein domain of unknown biochemical function implicated in bacterial signaling and regulation. In the plant pathogen Xanthomonas campestris pv. campestris , the synthesis of virulence factors and dispersal of biofilms are positively controlled by a two-component signal transduction system comprising the HD-GYP domain regulatory protein RpfG and cognate sensor RpfC and by cell–cell signaling mediated by the diffusible signal molecule DSF (diffusible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
522
1
26

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(562 citation statements)
references
References 28 publications
(49 reference statements)
9
522
1
26
Order By: Relevance
“…The role of protein-protein interactions involving RpfG in the regulation of virulence factor synthesis was examined by assessing in parallel the effects of alanine substitution of the residues of the GYP motif within RpfG and the effects of the mutation of the genes encoding the GGDEF target proteins XC_0249 and XC_0420. We previously have shown that expression of the HD-GYP domain of RpfG in the absence of the REC domain can restore the synthesis of virulence factors and motility in the rpfG mutant of Xcc to wild-type levels (6). These diverse regulatory effects are prevented by alanine substitution in the HD dyad (Fig.…”
Section: Rpfg-ggdef Interaction Regulates a Subset Of Rpfg-dependentmentioning
confidence: 93%
See 2 more Smart Citations
“…The role of protein-protein interactions involving RpfG in the regulation of virulence factor synthesis was examined by assessing in parallel the effects of alanine substitution of the residues of the GYP motif within RpfG and the effects of the mutation of the genes encoding the GGDEF target proteins XC_0249 and XC_0420. We previously have shown that expression of the HD-GYP domain of RpfG in the absence of the REC domain can restore the synthesis of virulence factors and motility in the rpfG mutant of Xcc to wild-type levels (6). These diverse regulatory effects are prevented by alanine substitution in the HD dyad (Fig.…”
Section: Rpfg-ggdef Interaction Regulates a Subset Of Rpfg-dependentmentioning
confidence: 93%
“…campestris (Xcc) has been shown to be the unsaturated fatty acid cis-11-methyl-dodecenoic acid (5). Both the synthesis and perception of the DSF signal require products of the regulation of pathogenicity factors (rpf) gene cluster (1,4,6). The synthesis of DSF is dependent on RpfF, which has some amino acid sequence similarity to enoyl CoA hydratases, whereas the two-component system comprising the sensor kinase RpfC and regulator RpfG is implicated in DSF perception and signal transduction (1,4,6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The only known effector domain that synthesizes c-di-GMP (designated as diguanylate cyclase activity, DGC) is the GGDEF domain. Two domains, EAL and HD-GYP, hydrolyze c-di-GMP (designated as phosphodiesterase activity, PDE) into linear 5Ј-phosphoguanylyl-(3Ј-5Ј)-guanosine (pGpG) or guanosine monophosphate (GMP), respectively (7)(8)(9)(10)(11)(12)(13). Many DGC proteins also contain an RxxD conserved motif 5 amino acids upstream from the GGDEF motif.…”
mentioning
confidence: 99%
“…Approximately 50% of proteins with characterized DGC activity (Römling et al, 2013) are regulated via allosteric control and the binding of cyclic di-GMP to a conserved inhibitory site (I-site) motif (RxxD) directly upstream of the GGDEF motif (Christen et al, 2006;Wassmann et al, 2007). Phosphodiesterase (PDE) proteins that possess EAL or HD-GYP domains are responsible for the depletion of cyclic di-GMP and conversion into 5¢-phosphoguanylyl-(3¢,5¢)-guanosine (pGpG) or two molecules of guanosine monophosphate (GMP), respectively (Ryan et al, 2006;Schmidt et al, 2005). Recently, oligoribonuclease (Orn) has also been identified to participate in the conversion of pGpG into GMP in Pseudomonas aeruginosa (Cohen et al, 2015;Orr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%